The lipid-dependent structure and function of LacY can be recapitulated and analyzed in phospholipid-containing detergent micelles - Vitrac, Heidi (Sci Rep, 2019)
Membrane proteins play key roles in cellular functions, their activity mainly depending on their topological arrangement in membranes. Structural studies of membrane proteins have long adopted a protein-centric view regarding the determinants of membrane protein topology and function. Several studies have shown that the orientation of transmembrane domains of polytopic membrane proteins with respect to the plane of the lipid bilayer can be largely determined by membrane lipid composition. However, the mechanism by which membrane proteins exhibit structural and functional duality in the same membrane or different membranes is still unknown. Here we show that lipid-dependent structural and functional assessment of a membrane protein can be conducted in detergent micelles, opening the possibility for the determination of lipid-dependent high-resolution crystal structures. We found that the lactose permease purified from Escherichia coli cells exhibiting varied phospholipid compositions exhibits the same topology and similar function as in its membrane of origin. Furthermore, we found several conditions, including protein mutations and micelle lipid composition, that lead to increased protein stability, correlating with a higher yield of two-dimensional crystal formation. Altogether, our results demonstrate how the membrane lipid environment influences membrane protein topology and arrangement, both in native membranes and in mixed detergent micelles.